Implementasi Aplikasi Augmented Reality Pembelajaran Matematika 3D Geometric Shapes Berbasis Android - Prima Putra; Sofa Sofiana (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
As technology develops rapidly, the use of information and communication technology in education has become an important factor to support teaching and learning activities to be effective and efficient. One of the uses of technology in education is to become a teaching aid for certain subjects. Mathematics is a subject that is considered difficult by most students due to the lack of media in learning as a tool to help students visualize mathematical concepts. 3D geometric shapes or building space is one example of material that can utilize augmented reality technology as a prop that can describe the shape of a real space. This study aims to produce applications that can help students understand the real form of building space with augmented reality technology and make students more enthusiastic in learning mathematics subjects, especially building materials.